The Effect Of User Readiness Acceptance Of Sijagger V2 Using Technology Readiness Acceptance Model (Tram) (CASE Research: KPPBC TMP A Tangerang) - Rudy Hermanto, Muchamad; Prasetio, Adhi; Ariyanti, Maya (Publisher Cv. Inara, 2023)
The digitization of the government system began with the declaration of the Electronic-Based Government System (SPBE) by President Jokowi in August 2018. The Directorate General of Customs and Excise (DGCE) implemented SPBE by building a Customs Excise Information System and Automation (CEISA) as its main service application, followed by the establishment of other applications other independent applications in the respective regional DGCE Work Units. The breakdown of the CEISA system in July 2021 caused a sizable national loss. To implement the SPBE and anticipate the occurrence of the same damage, KPPBC TMP A Tangerang built several independent applications to support customs and excise services, including Applications in the Tangerang network (SiJagger), Tangerang Customs Email (BeTa), Customs and Excise Service Email (PKC), Treasury Email, and Tangerang Certificate of Origin (SKA) Counter Email. To simplify the number of existing standalone applications, the SiJagger V2 application was created at KPPBC TMP A Tangerang as a replacement so that only one application is sufficient. This research aims to determine the Technology Readiness Index (TRI) of SiJagger V2 users, analyze the Technology Readiness Acceptance Model (TRAM) factors of these users for the SiJagger V2 application itself and to find out what needs to be improved to increase the readiness of the SiJagger V2 users. The data in this research were extracted using a quantitative method with data collection methods in the form of online questionnaires to 134 company respondents using SiJagger V2 in the supervision area of KPPBC TMP A Tangerang. Structural Equation Model (SEM) use as data analysis technique with SmartPLS program. The results from statistical test showed that the TRI index of SiJagger V2 users is included in the Low Technology Readiness category. The results showed that the TRI variables that affected the acceptance of the SiJagger V2 application at KPPBC TMP A Tangerang included the Optimism (OPT) and Innovativeness (INN) variables which had a significant positive effect, while the Discomfort (DIS) and Insecurity (INS) variables had a significant negative effect. Variables of TRAM that affect acceptance of SiJagger V2 application at KPPBC TMP A Tangerang include the variables Perceived ease of use (PEU), Perceived usefulness (PU), and Behavioral intention (BI) which have a significant positive effect, which is explained as follows: (1) OPT has positive significant effect on PEU, (2) OPT has positive significant effect on PU, (3) INN has positive significant effect on PEU, (4) INN has positive significant effect on PU, (5) DIS has negative significant effect on PEU , (6) DIS has negative significant effect on PU, (7) INS has negative significant effect on PEU, (8) INS has negative significant effect on PU, (9) PEU has positive significant effect on PU, (10) PEU has positive significant to BI, (11) PU has positive significant effect on BI. Results of this research are expected to be used as an evaluation of SiJagger V2 KPPBC TMP A Tangerang to be better so that SiJagger V2 users get customs and excise services faster and respond better, have a better experience in accessing information so that they are satisfied with the services provided by KPPBC TMP A Tangerang and increasing state revenue in the field of customs and excise.